2019
DOI: 10.3390/rs11192234
|View full text |Cite
|
Sign up to set email alerts
|

UoNGBR: A Regional Assimilation Barotropic Tidal Model for the Great Barrier Reef and Coral Sea Based on Satellite, Coastal and Marine Data

Abstract: All available satellite altimetry, coastal and marine data have been used to develop a new assimilative barotropic tidal model over the Great Barrier Reef (GBR) and Coral Sea using the Oregon State University Tidal Inverse Software (OTIS) with the specific consideration of bathymetry and drag coefficients. The model, named the University of Newcastle Great Barrier Reef (UoNGBR), has a 2′ × 2′ spatial resolution and includes 37 major and shallow water tidal constituents. The key to the development of UoNGBR is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The use of a constant drag coefficient across the GBR will alter the estimations of tides across the GBR. A previous study found that high‐resolution models coupled with spatially varying drag largely contribute to accurate estimates of tidal constituents across this region (Seifi et al., 2019). However, here, we found a better match to present‐day gauge data with a constant drag coefficient.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The use of a constant drag coefficient across the GBR will alter the estimations of tides across the GBR. A previous study found that high‐resolution models coupled with spatially varying drag largely contribute to accurate estimates of tidal constituents across this region (Seifi et al., 2019). However, here, we found a better match to present‐day gauge data with a constant drag coefficient.…”
Section: Resultsmentioning
confidence: 93%
“…To simulate tides in coral reef environments, unstructured mesh models are the best solution as they can fulfill the need for high resolution where needed (Lambrechts, Hanert, et al., 2008; Seifi et al., 2019; Storlazzi et al., 2011). The use of empirical models, using information regarding the sea‐level change from different techniques including satellite altimetry and tidal gauges, is not sufficient to capture the complexity of tides across the GBR system (Seifi et al., 2019). Previous studies of shifts in tidal dynamics due to SLR predict moderate to large variations in the tidal cycle, due to the sensitive nature of resonant or near‐resonant tidal basins regarding changes in bathymetry (Harker et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations